Ocular Examination of the Deaf Patient: Strategies, Accommodations, and Special Considerations. - Kiomall, Carly (Optometry & Visual Performance, 2019)
Deaf patients represent a subset of the population that may present to primary care optometrists. Deaf patients have a heightened need to maximize visual function due to their pre-existing sensory deficit. This clinical procedures manuscript aims to identify special considerations in the provision of eye care to deaf patients before, during, and after the exam encounter. Traditional methods of healthcare communication may need to be adjusted, and deaf cultural sensitivity is paramount. Specific examination strategies are discussed with the intent to equip the primary care optometrist with a particular skill set and additional resources in order to examine deaf patients efficiently and effectively.